Determination of the pathogenetic mechanisms for, and the diagnostic implications of, raised adenosine deaminase (ADA) levels in tuberculous exudates - Burgess, Lesley Jean (Stellenbosch : Stellenbosch University, 2012)
Thesis (Ph.D.) -- University of Stellenbosch, 1999.